Friday

November 21, 2014

November 21, 2014

Posted by **Cait** on Friday, January 5, 2007 at 3:06pm.

2^(k+3) = and < (k+3)!

i know how to do proving using mathematical induction when its just an equal sign, but I dont understand what to do when its an inequality.

thank you!!!

Here is what I would do

Step 1: check if it is true for k=1

that is: let k=1

2^4<= 4! ?

16<=24 ? YES

Step 2: assume it is true for k=n

or 2^(n+3) <= (n+3)! is true

Step 3: test to see if it is then true for k= n+1

or, is 2^(n+4) <= (n+4)! ??

subtract the two inequations (step 4 minus step3)

is 2^(n+4) - 2^(n+3) <= (n+4)! - (n+3)! ???

the left side factors to

2^(n+3)(2-1)

or 2^(n+3)

the right side is (n+4)*(n+3)! .... {just like 8! - 7! = 8*7!}

so we are looking at:

is 2^(n+3) <= (n+4)*(n+3)! ??

Well, the left side is the original left side of step 2, and the right side is the original right side of step 2 multiplied by a positive number > 1.

Since the right side was already >= the left side, muliplying it by a positive integer would cerainly make it even larger.

thank you lots!!

3467800

**Answer this Question**

**Related Questions**

mathematical induction - solve this using the mathematical induction : 1/1(3)+1/...

Mathematical induction. I'm stuck. So far I have.. - For all integers n ≥ ...

Calculus - Use mathematical induction to prove that the statement holds for all ...

AP Calc - Use mathematical induction to prove that the statement holds for all ...

Pre-Calculus - What makes a mathematical induction true? I know how to solve ...

advance algebra - 2(2^1) +3(2^2) + 4(2^3)+...+n^3 = [n(n+1)/2]^2 using the ...

advance algebra - 1(2)+2(3)+3(4)+...+n(n+1)= n(n+1)(n+2)/2 using the ...

math - how do you prove that (a-1) divides ((a^n)-1) evenly using mathematical ...

Math - Observe that : 1/1*3= 1/3 1/1*3+ 1/3*5= 2/5 1/1*3+ 1/3*5+ 1/5*7= 3/7 1/1*...

Math - Mathematical Induction - 3. Prove by induction that∑_(r=1)^n▒...